The contribution of intersectionality to quantitative research into educational inequalities. Issue 2 (25th June 2018) - Codiroli Mcmaster, Natasha; Cook, Rose
Abstract : Educational inequalities are one of the most critical issues facing contemporary societies. While there is a substantial body of quantitative literature tracking inequalities in education based on students' characteristics, an emerging literature is applying the concept of intersectionality to acknowledge the multiple, overlapping impact of these characteristics. We discuss the contributions of intersectionality to quantitative research on (vertical and horizontal) educational inequalities (attainment and subject choice). We then discuss the limitations inherent in this work, along with methodological innovations aimed at addressing these limitations. Finally, we make recommendations for researchers, to encourage greater use of intersectionality in quantitative educational research and thereby to deepen our knowledge of inequalities.